Competitividad en las Mipymes del sector comercio de la ciudad Latacunga - Armas Ochoa, Jonathan Bryan (2022)
The present investigation had as objective to determine the competitiveness index of the MiPyMes of commerce of the sector "La Matriz" of the city of Latacunga, for this the methodology proposed in the competitiveness map of the Inter-American Development Bank (IDB) was modified and used. , a population of 114 establishments that were registered in the cadastre of the Internal Revenue Service (SRI, 2022) was used. The survey used was made up of two sections, the first consisting of seven general questions, and the second section consisting of questions related to competitiveness made up of fifty questions, which consisted of a Likert scale from 1 to 5, where 1 represents never or not, 2 little, 3 regular, 4 good, and 5 excellent or fairly. For the validation of the instrument through statistics, Cronbach's Alpha, Kaiser-Meyer-Olkin (KMO) test and Barlett's test, both general and by dimensions, were used, the result of which allowed to verify the validity, fidelity and internal correlation. of the instrument variables. In addition, a Principal Component Analysis (PCA) was integrated into the research by means of a factorial analysis to group the variables in new dimensions. The results suggested that the general competitiveness of the MiPyMes of commerce of the sector "La Matriz" of the city of Latacunga have an average of 4,006 that corresponds to the range of Very Good; in question to the dimensions evaluated gave the following results: Strategic planning with 3,629; Operations with 4,163; Quality assurance with 4,375; Marketing with 3,936; Accounting and finance with 4,282; Human Talent with 3,794 and Environmental Management with 3,700. Finally, the analysis of principal components by means of factorial analysis allowed grouping the variables into thirteen factors that can be considered as: Activity planning, Business accounts, Marketing, Commercialization, Compliance with Regulations, Infrastructure, Waste management, Waste management. Goods, Traceability, Innovation, Environment, Competition and Quality Control. Which directly benefits the managers or owners of the companies to make correct decisions, in order to strengthen and grow their organizations, in addition to being competitive within the market, and the indirect beneficiaries for this project are businesses from other sectors. close to the commercial sector of this area that may have a higher level of clientele or improvement.